PENGARUH PERGAULAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR MATA PELAJARAN SOSIOLOGI SMAN 1 BATANG LUPAR - Oktavianida B. Upak; Sulistyarini Sulistyarini; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to determine the effect of peer relationships on students' learning motivation in sociology subjects in XI IIS class at SMA Negeri 1 Batang Lupar. The research method used in this research is quantitative research. The data sources of this research are 49 students of XI IIS class and the data is in the form of student questionnaire answer sheets. The results showed that peer association with the same percentage of age (47.66%), intimacy (41%), the group size (41%), and the cognitive development (40%) was included in the quite effective category. The students' learning motivation with the percentage of being diligent in facing assignments (41%), the tenacious in facing difficulties (43%), the interest in learning problems (42%), happy to work independently (41.5%), not bored in tasks activity (41.8 %), can defend opinions (46.5%) and enjoy solving problems (49%) are included in the category of quite effective. The influence of peer association on students' learning motivation in sociology subjects in XI IIS class at SMA Negeri 1 Batang Lupar obtained tcount 20.778 when compared with a table at a significant level of 5% of 2.011, then tcount> ttable (20.778 > 2.011) then, Ha is accepted. The magnitude of the influence of peer association on student motivation in SMA Negeri 1 Batang Lupar with a correlation coefficient value of 0.902. By the percentage of the contribution of peer association influence on learning motivation of 90.2%, while the remaining 9.8% is influenced by other variables that not examined in this research. Keywords: Learning Motivation, Peer Association, Sociology lesson